Early Career Members at the ERS International Congress London 2016: Early Career Forum - Bos, Lieuwe D.; Bartel, Sabine; Arranz, Inigo Ojanguren; Kahn, Nicolas; Mathioudakis, Alexander G.; Flood, Emma; Petrarca, Laura; Singanayagam, Aran; Hardavella, Georgia (Breathe, 2016)
Tweetable abstract ERSpublications - click to tweetThe @ERSTalk ECM Committee present highlights from #ERSLDN16 for Early Career Members http://ow.ly/tRYH305Owmz